Human rights in children's literature : imagination and the narrative of law - Todres, Jonathan; Higinbotham, Sarah (New York : Oxford University Press, 2015)
How can children grow to realize their inherent human rights and respect the rights of others? This book explores this question through children's literature from 'Peter Rabbit' to 'Horton Hears a Who!' to Harry Potter. The authors investigate children's rights under international law - identity and family rights, the right to be heard, the right to be free from discrimination, and other civil, political, economic, social and cultural rights - and consider the way in which those rights are embedded in children's literature.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on November 17, 2015).
Keywords: Children's literature -- History and criticism; Children's rights in literature